Seed banking impacts native Acacia ulicifolia seed microbiome composition and function - Dylan Russell; Vaheesan Rajabal; Matthew Alfonzetti; Marlien M. van der Merwe; Rachael V. Gallagher; Sasha G. Tetu (Environmental Microbiome)
Abstract Background Seed banks are a vital resource for preserving plant species diversity globally. However, seedling establishment and survival rates from banked seeds can be poor. Despite a growing appreciation for the role of seed-associated microbiota in supporting seed quality and plant health, our understanding of the effects of conventional seed banking processes on seed microbiomes remains limited. In this study we investigated the composition and functional potential of seed-associated bacterial epiphytes associated with stored and freshly collected seeds of a native plant, Acacia ulicifolia, using both 16S rRNA gene sequencing and culture-based approaches. Results Seeds obtained from seed banking facilities were found to host significantly less diverse bacterial populations, with substantial reductions in both low-abundance taxa and in community members commonly identified in freshly collected A. ulicifolia seeds. Bacteria with key plant growth promoting traits including IAA production, ACC deaminase activity, phosphate solubilisation, siderophore activity, and nitrogen fixation were identified in seed epiphytic communities, but these beneficial traits were less prevalent in stored seed compared to fresh seeds. Conclusion Overall, these results suggest that epiphytic seed microbiomes may undergo significant changes during the storage process, selecting for bacteria tolerant to storage conditions, and potentially reducing the population of plant-growth promoting bacteria on seeds.